Faktor–Faktor Yang Menyebabkan Terjadinya Hipertensi Pada Ibu Hamil Di RSIA Husada Bunda - Nurul Afifah; Luthfi , Amir; Apriyanti, Fitri (Evidence Midwifery Journal, 2024)
Hypertension for pregnant women (gestational) is the cause of 10-15% of complications in pregnancy and is part of the triad of complications besides bleeding and infection. The aim of the research is to find out the factors that cause high blood pressure in pregnant women at RSIA Husada Bunda in 2022. This type of research is quantitative research with a case control design. The number of respondents in this research was 47 cases (pregnant women with high blood pressure) and 47 controls (normal pregnant women without high blood pressure) using random sampling techniques. Data collection uses a checklist sheet. The data analysis used was univariate and bivariate analysis with the Chi Square test. The results of the univariate analysis showed that 49 respondents (52.1%) had normal nutritional status, 49 respondents (52.1%) had parity that was not at risk, as many as 58 respondents (61.7%) had jobs that were not at risk, and as many as 47 respondents (50.0%) had high blood pressure. The results of the Chi Square test, P value, namely 0.000 < 0.05, means that a link was found between nutritional status and cases of high blood pressure for pregnant women in the RSIA Husada Bunda area in 2022. RSIA Husada Bunda area in 2022, Pvalue is 0.000, meaning that a link between work and cases of high blood pressure was found for pregnant women in the RSIA Husada Bunda area in 2022.